Comprehensive expression profiles of CircRNAs, LncRNAs, and mRNAs in PBMCs from patients with the ossification of the posterior longitudinal ligament. (17th June 2021) - Jiang, Ning; Zhang, Kuibo; Shang, Jie; Wang, Bin; Zhong, Junlong; Wu, Biao; Li, Huizi; Xu, Xianghe; Lu, Huading
Abstract : Transcriptome expression profiles (circRNAs, lncRNAs, and mRNAs) were identified via high-throughput sequencing using PBMCs from OPLL and non-OPLL patients. Abstract : Ossification of the posterior longitudinal ligament (OPLL), one of spinal disease causing myelopathy, is characterized by the ectopic ossification and narrowing of the spinal cord. However, the pathogenesis of OPLL is largely unclear. In this study, transcriptome expression profiles (circRNAs, lncRNAs, and mRNAs) were identified via high-throughput sequencing using peripheral blood mononuclear cells (PBMCs) from OPLL and non-OPLL patients. We found that 1150 mRNAs, 331 circRNAs, and 1429 lncRNAs were significantly differentially expressed in the PBMCs of OPLL patients. GO and KEGG enrichment analyses revealed that most mRNAs were associated with inflammation. The co-expression networks indicated that circRNAs and lncRNAs could regulate the mRNAs through influencing the inflammation of OPLL. The circRNA–miRNA–mRNA integrated network showed that circRNA-regulated mRNAs associated with TGF-β and TNF-α signaling pathways. These analyses indicate that circRNAs, lncRNAs, and mRNAs from PBMCs might contribute to inflammation in OPLL.